Post-traumatic stress disorder in the military police of Rio de Janeiro: can a risk profile be identified? - Campos, Fernanda Dias (2021)
Background: Significant exposure to critical incidents characteristic of military police work has a potentially traumatic effect and multiple consequences for the mental health of these professionals, such as Post Traumatic Stress Disorder (PTSD). This study aims to investigate the occurrence of PTSD in this occupational group and its correlations with socio-demographic and occupational variables. Methods: This is a cross-sectional study of Rio de Janeiro’s Military Police officers (n = 3.577). Data was collected from self-reported questionnaires applied in an institutional health program. Post-Traumatic Stress Disorder Checklist—Civilian version was used to assess PTSD. Results: Rates of 16.9% for full PTSD and 26.7% for partial PTSD were found. Based on logistic regression analysis, female officers and police officers in lower ranks of the military hierarchy and performing administrative duties were found to be at most risk of developing PTSD. Conclusions: These results suggest the need to further understand the predictive organizational and individual variables of PTSD correlated with the increased vulnerability of professionals in order to contribute to institutional policies for the prevention and rehabilitation of these cases.